Testosterone Levels in Male Type-II Diabetic Patients and its Association with HBA1C Levels and Duration of the Disease - Laghari, Mubeena; Shaikh, Fozia; Murtaza, Shazia; Meraj, Munazzah; Shaikh, Farah (Journal of Liaquat University of Medical & Health Sciences, 2021)
Objective: To measure serum testosterone levels in type-II diabetes mellitus male subjects and to correlate its association with blood glycated haemoglobin A1 (HbA1C) levels and - duration of the disease. Methodology: This cross sectional study was carried out at Biochemistry department, LUMHS, Jamshoro, from December 2015 to May 2016. One hundred male subjects including 50 DM patients and 50 age matched with no family history of DM, were enrolled by purposive sampling technique. Study population excluded those patients diagnosed as diabetic erectile dysfunction, diabetic nephropathy, diabetic renal failure, metformin therapy, familial dyslipidemia, and hypercholesterolemia. Serum testosterone (ELISA assay) and whole blood HbA1C levels (TINIA assay) were measured by standard laboratory methods using Hitachi Roche Diagnostic Chemistry Analyzer. The obtained results were analysed by SPSS version 21.0(IBM, Incorporation, and USA) and is reported as Mean± SD. The p ? 0.05 was considered to indicate statistical significance. Results: The ages of diabetes mellitus patients and control subjects were 58.24±11.13 and 54.56±10.44 years respectively. Serum testosterone levels were observed to be more significant (p<0.004) in control subjects (3.53±0.74 mg /dL) and its levels decreased in diabetes mellitus patients (2.53±1.13 mg /dL). Similarly, HbA1C levels were significantly higher (p<0.0001) in diabetic subjects as compared to control subjects (8.40±1.27 vs 5.75±0.24%). Testosterone levels showed negative correlation with blood HbA1C levels and positive with duration of disease. Conclusion: In type 2 diabetic male patients serum testosterone levels demonstrated negative correlation with blood HbA1C levels and positive with duration of DM. Keywords: Serum testosterone, Type 2 diabetes mellitus, Glycated HbA1C